PENGEMBANGAN MEDIA STORYBOOK CERITA WAYANG BERGAMBAR BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN LITERASI MEMBACA SISWA KELAS V SEKOLAH DASAR NEGERI MULUR 03 - Fikrun Najih Hidayat; Para Mitta Purbosari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a picture storybook based on local wisdom and determine its feasibility in improving the reading literacy of fifth-grade students at Mulur 03 Public Elementary School. The study used the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analyze, design, develop, implement, and evaluate. The research subjects consisted of 24 fifth-grade students, one classroom teacher, as well as media and subject matter experts. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The data were analyzed using the Likert scale and the Guttman scale. The results showed that the developed storybook media obtained validation scores of 97% from media experts, 91% from subject matter experts, 97% from classroom teachers, and 100% from students, with an average score of 96%, which is categorized as highly valid. This illustrated puppet storybook media based on local wisdom has been registered for Intellectual Property Rights (IPR) and has been proven to increase students' interest, motivation, and reading literacy skills. Thus, this media is feasible for use as an alternative reading literacy learning media in elementary schools, especially in schools with limited technological facilities.